PENGARUH INVENTORY TURNOVER, TOTAL ASSET TURNOVER DAN NET PROFIT MARGIN TERHADAP PERUBAHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - E Janrosl, Viola Syukrina (Jurnal Manajemen Magister Darmajaya, 2015)
This study aims to analyze the effect of inventory turnover, total asset turnover, and net profit margin to changes in earnings in the automotive sector manufacturing companies listed in Indonesia Stock Exchange during the period 2010-2014. The research method in this study is a quantitative method by using financial statements to test the hypothesis that has been compiled to the variables to be studied. The results showed that the inventory turnover have a significant influence on changes in earnings is evidenced by the significant value of 0.014 <0.05, while the total asset turnover significance value of 0.519> 0.05 and a net profit margin of significance value of 0.081> 0.05 it can be concluded that the total asset turnover and net profit margin does not have a significant effect on earnings changes. Significant value 0.019 <0.05 this proves inventory turnover, total asset turnover, and net profit margin simultaneously significant effect on the change in earnings in manufacturing automotive sector from 2010-2014 listed in the Indonesia Stock ExchangeÂ Keywords: Inventory Turnover, Total Assets Turnover, Net Profit Margin, Changes In Earnings